Research on intrusion and large arch bulge in lining structure for highway’s mudstone tunnel - Li, Shuai; Fu, Jing; Liu, Gengren; Zhou, Jinghu (Frontiers in Physics, 2024)
During the construction of a highway in northwest China, large deformation of mudstone caused severe deformation of and damage to side walls, initial support, and secondary lining to various extents. To reveal the causes of mudstone's large deformation in the tunnels of this highway, a comprehensive study was conducted by using engineering geological survey, on-site monitoring and measurement, indoor rock mechanics test, numerical simulation, and macroscopic analysis. For the problem of large deformation of this highway's tunnel section from YK209+500m to YK210+030m, the 3D finite difference method FLAC 3D was used to simulate the large deformation of the wall rock and compare the deformation of the tunnel and the mechanical characteristics of the lining structure under different conditions by means of inverse analysis of the rheological characteristics of the mudstone and simulation of the softening of the mudstone in water. The research results provide a reference and basis for the construction design of similar mudstone tunnel projects. For the management of tunnel deformation, it is recommended to enhance the tunnel's drainage measures, thereby mitigating the intensification of mudstone softening when exposed to water.